Impact of Covid-19 on the Outcomes of Basic Immunization in Health Facilities - Retno Setyo Iswati; Indria Nuraini (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
The purpose of this study was to determine the impact of Covid 19 on basic immunization coverage, oriented to the number of Covid 19 cases mapped in the red, yellow, and green. This research provides the advantage of making a policy to improve children's health during a pandemic, particularly in preventing diseases that can be anticipated by immunization, such as tuberculosis, diphtheria, hepatitis, tetanus, meningitis, polio, and measles. This research can also be used as a basic for immunization in health facilities while still implementing health protocols. This study's results can be implemented in primary health facilities such as the Puskesmas, Posyandu, Poskesdes, or Midwife Independent Practice. This study's results indicate that immunization coverage <95% is mostly found in the red zone area of Pentabio 1 and 2 immunization, as well as measles. Chi-square test found that there was no significant relationship with basic immunization coverage.